Penyusunan Bibliografi Beranotasi Ilmu Kepolisian di Perpustakaan Kepolisian Daerah Sumatera Barat - Putri, Nabella; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
Abstract The purpose of this study were to describe of making an annotated bibliography of police science in the Library of Police Regional West Sumatera and can be used to find information needed quickly and easily, to describe of constraints an annotated bibliography of police science in the Library of Police Regional West Sumatera and to describe of efforts an annotated bibliography of police science in the Library of Police Regional West Sumatera. The method used in this study is descriptive method. With data collection techniques through direct observation and interviews. In making an annotated bibliography there are eight stage is: (1) determination of the title bibliography; (2) the collection books; (3) the selection of library materials; (4) gruping or classification; (5) keyword creation; (6) indexing based an author index, title index, and keyword index; (7) typing bibliography textx;(8) the final bibliography examination. And to describe of the solution and effort of making an bibliography of the book with the subject of police science in the Library of Police Regional West Sumatera.Keywords: annotated bibliography; book of police science